2015
DOI: 10.1007/s00775-015-1273-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the catalytic role of active site residues in the Fe-type nitrile hydratase from Comamonas testosteroni Ni1

Abstract: A strictly conserved active site arginine residue (αR157) and two histidine residues (αH80 and αH81) located near the active site of the Fe-type nitrile hydratase from Comamonas testosteroni Ni1 (CtNHase), were mutated. These mutant enzymes were examined for their ability to bind iron and hydrate acrylonitrile. For the αR157A mutant, the residual activity (kcat = 10 ± 2 s −1 ) accounts for less than 1 % of the wild-type activity (kcat = 1100 ± 30 s −1 ) while the Km value is nearly unchanged at 205 ± 10 mM. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Some of the most important amino acids in NHase are βArg52 and βArg157, coordinating the active site by hydrogen bonds with post-translationally modified cysteines ( Figure 9 a) [ 30 ]. After mutating one of these residues, NHase loses catalytic activity [ 31 , 32 ]. The distances between Cζ atoms of the two arginine residues and the modified active-site cysteines were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the most important amino acids in NHase are βArg52 and βArg157, coordinating the active site by hydrogen bonds with post-translationally modified cysteines ( Figure 9 a) [ 30 ]. After mutating one of these residues, NHase loses catalytic activity [ 31 , 32 ]. The distances between Cζ atoms of the two arginine residues and the modified active-site cysteines were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis on these sites resulted in dramatic decrease of k cat values. Further structural study indicated that disruption of the hydrogen bonding interactions in mutant enzyme probably altered the nucleophilicity of the sulfenic acid oxygen and the Lewis acidity of the active site Fe (III) ion (Martinez et al, 2015).…”
Section: Catalytic Mechanism Of Nhasementioning
confidence: 99%